Efficiency of initial presbyopia functional correction in visually intensive work persons - I. G. Ovechkin; N. N. Agafonov; V. E. Judin (Oftalʹmologiâ)
Aim: To study the efficacy of functional (physiotherapeutic) stimulation of an eye in visually intensive work patients with the initial symptoms of presbyopia.Methods: 104 visually intensive work patients before and after complex physiotherapy (low-energy laser radiation, magnitotherapy, stimulation of accommodation) were examined.Results: Physiotherapy improved near vision (by 0.16 RU on average) and subjective psychophysiological status (by 11.8 %) and reduced eye strain (by 2.1 times). Additionally, objective accommodography indices improved, brightness sensitivity thresholds decreased by 16.5 %, and psychological status improved by 18.2 %. These positive effects of physiotherapeutic stimulation enabled to delay eyeglasses prescription for 6 months in 76 % of patients and for 9 months in 42 % of patients.Conclusion: Functional (physiotherapeutic) stimulation provides effective correction of initial presbyopia in visually intensive work persons.